Pengaruh Strategi Pemasaran Pondok Pesantren Berbasis Digital Terhadap Minat Peserta Didik - Yanti, Riska Fikri; Hidayat, Wahyu; Mulyani, Heny (PT. Cahya Edupreneur Indonesia, 2025)
The development of information technology has encouraged Islamic boarding schools to utilize digital media, such as websites, Instagram, YouTube, TikTok, Facebook, WhatsApp, and other online communication platforms, as a means of promotion and information dissemination. This digital marketing strategy is expected to attract attention, foster interest, arouse desire, and encourage prospective students to register and become part of the Islamic boarding school. This study aims to: (1) Determine the digital-based Islamic boarding school marketing strategy at the Al-Aqsha Modern Islamic Boarding School in Jatinangor, Sumedang. (2) Determine student interest at the Al-Aqsha Modern Islamic Boarding School in Jatinangor, Sumedang. (3) Analyze the influence of digital-based Islamic boarding school marketing strategies on student interest at the Al-Aqsha Modern Islamic Boarding School in Jatinangor, Sumedang. This study uses a quantitative approach with descriptive methods. Data collection in this study was obtained through a questionnaire with a Likert scale data measurement. The respondents of this study were 61 10th grade high school students at the Al-Aqsha Modern Islamic Boarding School in Jatinangor, Sumedang. The results of the study indicate that (1) the digital-based Islamic boarding school marketing strategy at the Al-Aqsha Modern Islamic Boarding School in Jatinangor, Sumedang, obtained an average score of 3.83. This score is classified as